MANAGING PRODUCT RELIABILITY IMPROVEMENT PROJECTS - Gembong Baskoro (Institute of Research and Community Outreach - Petra Christian University, 2005)
Product reliability improvement projects have shown promising results for industries to preserve customer satisfaction. Therefore, best practices on reliability improvement in industries that operate in high volume consumer product can be used as a reference toward managing product reliability improvement. In reliability improvement the method should not only focus on how to achieve the expected deliverable but also to sustain the improvement itself and to close the improvement loop. The importance of managing product reliability improvement is on how to ensure that the project moves to the right direction without loosing its flexibility.